Potential Role of SWI/SNF Complex Subunit Actin-Like Protein 6A in Cervical Cancer - Wang, Qingying; Cao, Zuozeng; Wei, Yingze; Zhang, Jiawen; Cheng, Zhongping (Frontiers in Oncology, 2021)
SWI/SNF complex subunit Actin-like protein 6A (ACTL6A) has been regarded as an oncogene, regulating the proliferation, migration and invasion of cancer cells. However, the expression pattern and biological role of ACTL6A in cervical cancer have not been reported. In this study, the mRNA expression and protein level of ACTL6A in cervical cancer samples were determined by public database and immunohistochemical (IHC) analysis. The effects of ACTL6A on cervical cancer cells were investigated via MTT, colony-formation assay, tumor xenografts and flow cytometry. Gene set enrichment analysis (GSEA) was used to explore the potential mechanism of ACTL6A in regulating tumorigenesis of cervical cancer. The results revealed that ACTL6A was markedly upregulated in cervical cancer tissues. Silencing ACTL6A expression resulted in decreased cervical cancer cell proliferation, colony formation and tumorigenesis in vitro and in vivo. Furthermore, we demonstrated that knockdown of ACTL6A induced cell cycle arrest at G1 phase, ACTL6A-mediated proliferation and cell cycle progression were c-Myc dependent. Our study provides the role of ACTL6A in cervical oncogenesis and reveals a potential target for therapeutic intervention in this cancer type.